The clinical outcomes of fresh versus frozen embryos transfer in women ≥40 years with poor ovarian response - Conghui Liu; Yu Li; Hong Jiang; Yingchun Liu; Xiaomin Song (Korean Society of Obstetrics and Gynecology, 2021)
Objective To compare the clinical outcomes of fresh embryo transfers (ETs) and frozen-thawed embryo transfers (FETs) after a freeze-all cycle in women ≥40 years old with poor ovarian response (POR). Methods We performed a single-center, retrospective, case-control study of patients who underwent in vitro fertilization between January 2014 and June 2019. We included a total of 192 patients aged 40 years or older from whom 3 or fewer oocytes had been retrieved and who were receiving cleavage-stage ET in this study. Of these patients, 101 and 91 patients underwent fresh ET and FET, respectively. The primary outcome was the live birth rate (LBR) after the first ET. Logistic regression analysis was used to compare the IVF outcomes and neonatal characteristics between the fresh ET and FET groups, adjusting for maternal age, body mass index, luteinizing hormone, and the number of good quality embryos transferred. Results The mean maternal ages and number of oocytes retrieved (43.2 years and 2.3 in both groups, P=0.902 and P=0.927, respectively) were similar in the fresh ET and FET groups. No significant difference was observed between the LBRs of the fresh ET and FET groups (adjusted odds ratio, 1.28; 95% confidence interval, 0.29-5.70). The clinical pregnancy and miscarriage rates, and neonatal characteristics (birth weights and premature infant rates) were similar between the 2 groups. Conclusions FET after the freeze-all strategy had no beneficial impact on the clinical outcomes of women ≥40 years with POR.